ds coordinate geometry : DS Archive
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 18 Jan 2017, 00:59

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# ds coordinate geometry

Author Message
Director
Joined: 24 Oct 2005
Posts: 659
Location: London
Followers: 1

Kudos [?]: 14 [0], given: 0

### Show Tags

21 Mar 2006, 08:51
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

### HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

In the xy plane, does the line with equation y = 3x + 2 contain the point (r,s)?

1) (3r + 2 - s)(4r+ 9 - s) = 0
2) (4r - 6 - s) 93r + 2 - s) = 0

Manager
Joined: 09 Feb 2006
Posts: 129
Location: New York, NY
Followers: 1

Kudos [?]: 7 [0], given: 0

### Show Tags

21 Mar 2006, 10:46
In the xy plane, does the line with equation y = 3x + 2 contain the point (r,s)?

1) (3r + 2 - s)(4r+ 9 - s) = 0
2) (4r - 6 - s) (3r + 2 - s) = 0

The math here is slightly complicated -- almost too complicated to do in two minutes to ensure that you have the correct answer.

The question can be restated as: Is s = 3r + 2

Statement 1:

12r^2 + 35r - 7rs - 11s + s^2 + 18 = 0

Now, we can relate r to s using the original equation, y = 3x + 2, by plugging in those variables

s = 3r + 2

If the equation can be resolved to this, then we have an answer. Let's solve for s
12r^2 + 35r - 7rs - 11s + s^2 + 18

s^2 - (11 + 7r)s = -12r^2 - 35r - 18

At this point, we can't solve for s (at least I'm 99% sure that we can't -- unless someone can show me another way).

Inconclusive, so we have to go to statement 2

Statement 2:

12r^2 - 10r - 7rs + 4s + s^2 -12 = 0
We run into the same problem here, so inconclusive

Statements 1 & 2:
12r^2 + 35r - 7rs - 11s + s^2 + 18 = 12r^2 - 10r - 7rs + 4s + s^2 -12

Which equals:

45r - 15s + 30 = 0

15s = 45r + 30
Therefore, s = 3r+2

Manager
Joined: 04 Jan 2006
Posts: 58
Followers: 1

Kudos [?]: 2 [0], given: 0

### Show Tags

21 Mar 2006, 14:21
Do we really have to go through that lengthy procedure?

stmt1:
1) (3r + 2 - s)(4r+ 9 - s) = 0
->s = 3r+2 or s= 4r+9
In suff

stmt2:
2) (4r - 6 - s) 93r + 2 - s) = 0
s= 3r+2 or s= 4r-6
Insuff

Combining both
s has a common value s= 3r+2

So C
Manager
Joined: 09 Feb 2006
Posts: 129
Location: New York, NY
Followers: 1

Kudos [?]: 7 [0], given: 0

### Show Tags

21 Mar 2006, 14:29
Much better way to solve. Good call.
Director
Joined: 24 Oct 2005
Posts: 575
Location: NYC
Followers: 1

Kudos [?]: 59 [0], given: 0

### Show Tags

21 Mar 2006, 18:51
Nayan wrote:
Do we really have to go through that lengthy procedure?

stmt1:
1) (3r + 2 - s)(4r+ 9 - s) = 0
->s = 3r+2 or s= 4r+9
In suff

stmt2:
2) (4r - 6 - s) 93r + 2 - s) = 0
s= 3r+2 or s= 4r-6
Insuff

Combining both
s has a common value s= 3r+2

So C

I understand how you got s = 3r + 2.. but what I dont understand is that why having 3r + 2 in both the equations makes the answer C..
_________________

Success is my only option, failure is not -- Eminem

21 Mar 2006, 18:51
Display posts from previous: Sort by